2013
DOI: 10.1074/jbc.m113.486944
|View full text |Cite
|
Sign up to set email alerts
|

A Platform to View Huntingtin Exon 1 Aggregation Flux in the Cell Reveals Divergent Influences from Chaperones hsp40 and hsp70

Abstract: Background: How misfolded proteins such as mutant huntingtin aggregate in the cell remains enigmatic.Results: We built a platform to view how aggregation proceeds and assessed the impact of quality control chaperones hsp40 and hsp70.Conclusion: hsp70 enhanced survival of cells with aggregates; hsp40 suppressed aggregation.Significance: We developed a new toolkit to illustrate the impact of protein aggregation on cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…Data show transfection efficiency as standardized to a gate (FITC channel) defining 98% background fluorescence using untransfected cells as a reference. The percentage of transfected cells with inclusions was defined using PulSA as described previously (11,12), with the nonaggregating mutants to set the reference gate positions (n ϭ 3; mean Ϯ S.D. are shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data show transfection efficiency as standardized to a gate (FITC channel) defining 98% background fluorescence using untransfected cells as a reference. The percentage of transfected cells with inclusions was defined using PulSA as described previously (11,12), with the nonaggregating mutants to set the reference gate positions (n ϭ 3; mean Ϯ S.D. are shown).…”
Section: Resultsmentioning
confidence: 99%
“…SVA is a benchmark method for investigating mass heterogeneity of purified proteins (13), but to date has had limited application in cell lysates using fluorescently tagged proteins. We applied this method successfully to cell lysates to decipher the aggregation patterns of Httex1 and other proteins (10,12,14). We have also developed a strategy to separate cells expressing mutant protein enriched in inclusions from those lacking inclusions using Pulse Shape Analysis (PulSA) by flow cytometry, which enables a second layer of control over the study of protein oligomerization in cells with visible inclusions or not (11).…”
mentioning
confidence: 99%
“…Development of techniques that enable the aggregation state of α-syn to be tracked in cells, such that this can be linked to specific biological outcomes, would greatly assist future work in this area. For example, the development of conformational sensors of α-syn capable of distinguishing monomeric, oligomeric and fibrillar species, such as those developed for Htt (Ormsby et al 2013), would facilitate investigation of the precise mechanism(s) by which sHsps act to prevent α-syn aggregation in cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, N2a cells represent a well-established neuronal model used for characterising intracellular protein aggregation (Krishnan et al 2006;Ojha et al 2011;Ormsby et al 2013;Chai et al 2016). Cells were cultured in Dulbecco's modified Eagle's medium/Ham's Nutrient Mixture F12 (DMEM/F12; ThermoFischer Scientific, Waltham, USA) supplemented with 10% (v/v) foetal bovine serum (FBS; Bovagen Biologicals, East Keilor, Australia) and 2.5 mM L-glutamine (ThermoFischer Scientific, Waltham, USA).…”
Section: Culture and Transfection Of Mammalian Cell Linesmentioning
confidence: 99%
“…Furthermore, this interaction may actually help mediate the coalescing of the aggregates into larger protein deposits. There is evidence that protein inclusions are protective in the cell; studies have reported a lack of correlation between amyloid deposition in the brain and disease progression (Schmitz et al 2004 ;Rabinovici and Jagust 2009 ), and in cell culture models of protein aggregation multiple inclusions can be present in otherwise 'healthy' cells (Arrasate et al 2004 ;Gong et al 2008 ;Ormsby et al 2013 ). Thus, by promoting the formation of inclusions sHsps may assist in shielding the cell from toxic oligomers.…”
Section: Interactions With Amyloid Fibrilsmentioning
confidence: 94%